Regulation of Personal Vaporizer Sales to Children in Indonesia - Herlina, Maxima Nevlita; Budiarsih, Budiarsih (Universitas PGRI Madiun, 2024)
Smoking, including among minors, is a worrying phenomenon in Indonesia, mainly due to the rapid development of the environment and lack of supervision. This study aims to analyze legal protection for minors regarding the use of personal vaporizers, considering the health risks associated with smoking and vaping habits. This research uses a normative legal approach, utilizing primary and secondary sources to examine the existing legal framework and its implementation. The results show that laws in Indonesia, such as the Child Protection Law and the Consumer Protection Law, recognize the rights of children and consumers, including their safety and protection from dangerous substances. However, specific regulations regarding personal vaporizers and their sale to minors still do not exist, resulting in ambiguity for the business world and inadequate protection for minors. The recommendations given include strengthening regulations, providing strict administrative sanctions to violators, increasing educational campaigns, and increasing parental and community involvement in preventing underage smoking and vaping. Ultimately, a comprehensive approach involving legal reform, law enforcement, and awareness-raising efforts is critical to safeguarding the health and well-being of minors in Indonesia.